Phonon localization by mass disorder in dense hydrogen-deuterium binary alloy - Howie, Ross T; Magdău, Ioan B; Goncharov, Alexander F; Ackland, Graeme J; Gregoryanz, Eugene (Physical review letters, 2014)
Using a combination of the Raman spectroscopy and density functional theory calculations on dense hydrogen-deuterium mixtures of various concentrations, we demonstrate that, at 300 K and above 200 GPa, they transform into phase IV, forming a disordered binary alloy with six highly localized intramolecular vibrational (vibrons) and four delocalized low-frequency (<1200  cm(-1)) modes. Hydrogen-deuterium mixtures are unique in showing a purely mass-induced localization effect in the quantum solid: chemical bonding is isotope-independent while the mass varies by a factor of 2.